From Subjective Cognitive Complaints to Dementia: Who Is at Risk?: A Systematic Review. (March 2016) - Mendonça, Marcelo D.; Alves, Luísa; Bugalho, Paulo
Subjective cognitive complaints (SCCs) are frequent in the elderly population. The majority of individuals with subjective complaints never progress to significant cognitive decline, but some of them have a higher risk of progression to objective cognitive impairment than persons with no cognitive concerns. We performed a systematic review of community-based studies that focused on the progression risk associated with SCC and on the complainers' characteristics associated with progression. Seventeen studies were included. As a group, SCCs are associated with a significantly higher risk of progression to dementia. Worried complainers, persons who refer an impact of their complaints on activities of daily living, and those whose complaints are also noticed by an informant have the highest risk of progression. Taking into account the fluctuating course of SCC and their frequent reversion, care should be taken to not overvaluate them. Further studies are necessary to better define risk features.